IMPLEMENTATION OF ADMINISTRATIVE MEASURES IN STATE ADMINISTRATIVE (TUN) DISPUTES - Bambang Herianto; Abdul Rahman Maulana Siregar (Universitas Efarina, 2023)
The implementation of Regulation of the Supreme Court of the Republic of Indonesia (PERMA) Number 6 of 2018, dated 4 December 2018 concerning Guidelines for Settlement of Government Administrative Disputes after taking administrative measures, which is a further regulation of the provisions in Articles 75, 76 and Article 77 of Law Number 30 of 2014 concerning Government Administration, bringing about changes in the state administrative justice system in Indonesia, namely relating to administrative efforts. This then raises issues regarding first, whether administrative measures are an obligation that must be taken first before filing a state administrative dispute lawsuit with the PTUN; and secondly, what are the legal procedures for making objections to State Civil Service (ASN) employment disputes; and thirdly what are the legal consequences of non-implementation of administrative efforts by the Plaintiff. The aim of this research is to analyze and describe the application of administrative efforts to state administration disputes. Normative juridical research methods are used to answer this problem. The results of the research show that administrative efforts must be carried out as legal protection for the people in State administrative disputes, and the legal procedure for making objections to ASN disputes is regulated in Article 129 of Law Number 5 of 2014 concerning State Civil Apparatus, and the Judge will reject the Plaintiff if not. take available administrative measures.